Music Video as a Poetic Interpretation - Alisa S. Bodyanskaya; Kapitalina V. Sinegubova (Виртуальная коммуникация и социальные сети, 2023)
This article introduces the phenomenon of videopoetry as a hybrid product of mass media whose popularity is based on intermediality, i.e., the cumulative effect on different perception channels. Videopoetry is a productive form of verbal creativity in the contemporary media culture with its active reception of art. The research featured poems by W. B. Yeats, T. S. Eliot, and W. H. Auden presented as videos and the way they respond to someone else's poetic word. The authors analyzed 15 videos by comparing the original text and the video sequence in line with the method developed by N. V. Barkovskaya and A. A. Zhitenev. The analysis revealed several options for relaying a poetic work as a music video. Three videos provided a direct illustration of the source text, suggesting a complete or partial visual duplication of the original poetic imagery. Five videos offered an indirect illustration of the source text by using associative images in relation to the central images of the poem. Five videos gave a minimal illustration: the picture did not dominate the text of the poem, but its choice implied a certain interpretation. Two videos featured the video maker as a reciter. The video makers did not try to transform the poetic text but used the video sequence as a way to enter into a dialogue with the original poem or resorted to indirect illustration to generate occasional meanings. Thus, video makers keep the original text unchanged and see the video sequence and musical accompaniment as their responsibility but maintain a dialogue between the original text and its game reinterpretation.